Modeling of Causes of Sina Weibo Continuance Intention with Mediation of Gender Effects - Wang, Lingyu; Zhao, Wenguo; Sun, Xianghong; Zheng, Rui; Qu, Weina (Frontiers in Psychology, 2016)
Sina Weibo is a Twitter-like social networking site and one of the most popular microblogging services in China. This study aims to examine the factors that influence the intentions of users to continue using this site. This paper synthesizes the expectation conﬁrmation model (ECM), constructs of habit and perceived critical mass, and the gender effect to construct a theoretical model to explain and predict these user intentions. The model is then tested via an online survey of 498 Sina Weibo users and partial least squares (PLS) modeling. The results indicate that the continuance intention of users is directly predicted by their perceived usefulness of the service (β=0.299), their satisfaction (β=0.208), and their habits (β=0.389), which jointly explain 65.9% of the variance in intention. In addition to the effects of these predictors on the continuance intentions of Sina Weibo users, an assessment of the moderating effect of gender suggests that habit plays a more important role for females than for males in continuance intention, but perceived usefulness seems to be more important for males than for females. The implications of these findings are then discussed.